Adsorption of methylene blue from aquoues solution by using imprata cylindrica waste - Fatin Nadia, Pauzi (2015)
Dyes are widely used in many industries, mainly in the textile industries. The effluents containing these dyes are an environmental concern and the disposal of these wastes into receiving water causes damage to the environment and may also be toxic to aquatic life. It is therefore imperative to treat textile effluents due to their toxic and aesthetic impacts on the receiving water bodies (Vadivelan and Kumar, 2005; Hameed and El-Khaiary, 2008). Removal of dyes from wastewater using adsorption process has become one of the most effective and comparable low cost methods for the decolourization of textile wastewater (Mckay et al,1999 ; Khan et al, 2002). Adsorption by using activated carbon is a very effective process, but the high cost of such adsorbents has motivated the search for alternatives and low-cost adsorbents. Agricultural waste is alternative use for wastewater treatment because they are cheap, simple, sludge free and involve small initial cost and investment This work explores the feasibility of Imperata Cylindrica (IC), a solid waste, abundantly available in Malaysia, for the absorption of methylene blue (MB). Batch adsorption studies were conducted to evaluate the effects of adsorbent dosage (0.25-2 g/L), initial pH (2-8), initial concentration (50-400 mg/L), and temperature (30-50 ºC). The optimum conditions were achieved at 1 g/L of adsorbent dosage, pH 6, 400 mg/L initial dye concentration and at 40 ºC, with adsorption capacity of 314.06 mg/g. The adsorption of MB into the surface of IC was confirmed by SEM image for IC before adsorption and after 50 min adsorption process. The experimental data were analyzed by the Langmuir and Freundlich isotherms, and were found to follow the Freundlich isotherm model with coefficients of correlation R2 ≥ 0.9876 indicating that the ongoing process is heterogeneous in nature. Pseudo-first-order and pseudo-second-order kinetics models were tested with the experimental data, and pseudo-second-order kinetics was the best for the adsorption of MB by IC with coefficients of correlation R2 ≥ 0.999 for all initial MB concentrations studied. Thermodynamic parameters such as ΔHo, ΔGo and ΔSo clearly indicated that the adsorption behaviour of the system is endothermic, feasible and increasing randomness at temperature range of 30-40 oC, while, at temperature range of 40-50 oC, the ongoing process is exothermic, feasible and decreasing randomness. The results revealed that IC is potentially low-cost adsorbent for adsorption of MB